INSTAGRAM VS REALITY: INFLUENCE OF INSTAGRAM ON DEPRESSION AMONG ADOLESCENTS AND YOUNG ADULTS - A LITERATURE REVIEW - Oliwia Gugała; Kamil Nowak; Alicja Stryczek-Schlusche; Hanna Paszkiewicz; Patryk Kowalczyk; Bartłomiej Trzciński; Igor Winogrodzki; Aleksandra Magdalena Furczyńska; Filip Bracichowicz; Aleksandra Gęsińska; Wiktoria Socha (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: The vast majority of the global population has access to the internet and consequently to social networking services (SNSs). These are online social media platforms that facilitate interaction between users and enable the sharing of information. One of the most popular SNSs is Instagram. However, the utilisation of this application does exert an influence on the mental health of users, yielding both favourable and unfavourable outcomes. This study aims to review the literature on the correlation between Instagram use and depression among the largest group of users – adolescents and young adults. Stage of knowledge: Instagram is a free application for sharing photos and videos which has rapidly become an integral part of life for many people around the world. Due to the visual nature of its content, this social networking platform possesses characteristics that differentiate it from other such services, making it worthwhile to investigate the effects of this medium on mental health. Given its popularity, particularly among young users, studying the correlation between Instagram and a range of psychological well-being variables can provide valuable insights into its impact on the mental health of adolescents and young adults, such as depression. Materials and methods: A comprehensive literature review was conducted utilising the Google Scholar and PubMed databases, employing the following keywords: Instagram, Social Networking Services, Depression, Mental Health, Adolescents, Young Adults. Results: Unlimited access to social networking services has an impact on the mental health of users. Specifically Instagram use can lead to unfavorable results on mental well-being, such as depression. The group most vulnerable to these negative consequences is also the largest group of users – adolescents and young adults. Conclusions: Further research on the influence of Instagram on depression among adolescents and young adults is essential to gain a more profound understanding of their mental health and to identify effective methods of preventing the adverse outcomes associated with social media use, such as depression. Furthermore, the potential of Instagram as a medium for promoting mental health should be given due consideration.